Institutional Reform and the Judiciary : Which Way Forward? - Islam, Roumeen (World Bank, Washington, DC, 2014)
The author presents some general lessons in institution-building that has relevance for judiciary reform. She emphasizes the value of simplicity in design commensurate with country capacity, the importance of innovation and experimentation, and of economic openness in effective institution-building. The author underscores how the incentives of individuals depend on both the details of institutional design within the judiciary and also some critical institutions external to the judiciary. Finally she argues for the need to ground reform initiatives on a solid empirical and comparative approach. The author illustrates some of these issues by drawing on a recent project conducted by the World Bank and other institutions.